Comprehensive Measurement and Analysis of Traffic Noise Along The Changlun-Kuala Perlis Highway - Tan Wei Hong; Stephanie Kew Yen Nee; Amares Singh; Teoh Choe Yung; Mohammad Salman Khan Nazaruddin (International Journal of Integrated Engineering, 2025)
Road traffic noise, encountered by residents living close to major highway routes, has emerged as one of the most prevalent environmental concerns in recent years. Increasing noise levels result hugely from greater vehicles on the road, higher speeds, and heavier traffic volumes. However, the tire-pavement interaction often constitutes the most prominent noise source on highways. Some studies have discovered that prolonged exposure to highway noise is likely associated with hearing loss and other health problems. Notwithstanding its severity, data available on transport noise emission from highways in Malaysia is still lacking. Therefore, this study aims to analyze the traffic noise index (TNI) and noise pollution level (NPL) in dBA to assess the traffic noise impact along the Changlun-Kuala Perlis Highway, near the residential areas. Different noise indices, including equivalent continuous noise level (LAeq), maximum permissible 10% (L10) and 90% (L90) noise level, and maximum peak noise level (LAFmax) were all determined. The noise level status was also identified based on the measured noise indices to calculate the TNI and NPL. In this present study, the acoustic measurement was performed at various residential areas along the highway through the NoiSee application, which provides a readout of the noise level, using an external calibrated built-in microphone. Results revealed that all residential areas face a traffic noise disturbance with a DOE standard of more than 65 dBA, and 96% of them have TNI values higher than 74 dBA, with 70% of NPL that were below 88 dBA. As indicated by the analysis, it is clear that the residential areas along Jalan Changlun-Kuala Perlis were heavily affected by the traffic noise emitted from highways.